Land use change converts temperate dryland landscape into a net methane source - Uthara Vengrai; Katherine M. Tucker; William K. Lauenroth; Ingrid C. Burke (Ecosphere, 2025)
Abstract Drylands cover approximately 40% of the global land surface and are thought to contribute significantly to the soil methane sink. However, large‐scale methane budgets have not fully considered the influence of agricultural land use change in drylands, which often includes irrigation to create land cover types that support hay or grains for livestock production. These land cover types may represent a small proportion of the landscape but could disproportionately contribute to land–atmosphere methane exchange and are currently omitted in estimates of dryland methane fluxes. We measured methane fluxes among big sagebrush, introduced wetlands, and hay meadows in a semiarid temperate dryland in Wyoming, USA, to investigate how these small‐scale irrigated land cover types contributed to landscape‐scale methane dynamics over the summer of 2021. Big sagebrush ecosystems dominated the landscape, while the introduced wetlands and hay meadows represented approximately 1% and 12%, respectively. Methane uptake was consistent in the big sagebrush ecosystems, emissions and uptake were variable in the hay meadows, and emissions were consistent in the introduced wetlands. Despite making up 1% of the total land area, methane production in the introduced wetlands overwhelmed consumption occurring throughout the rest of the landscape, making this region a net methane source. Our work suggests that introduced wetlands and other irrigated land cover types created for livestock production may represent a significant, previously overlooked source of anthropogenic methane in this region and perhaps in drylands globally.